Patient safety : perspectives on evidence, information and knowledge transfer - Zipperer, Lorri A., 1959- (Farnham, Surrey, England ; Burlington, VT, USA : Gower, 2014)
This book'provides background on the patient safety movement, systems safety, human error and other key philosophies that support change and innovation in the reduction of medical error. The book draws from the multidisciplinary areas within the acute care environment to provide models that support proactive changes in how team-based improvement efforts can affect the knowledge provision necessary to support safe care delivery. The publication discusses how the tenets of safety (described in the beginning of the book) have been or can be actively applied in the field. Tools and case studies, in addition to a brief discussion of core resources, are included. The key objectives of the book: To inform healthcare leadership, clinical directors, risk managers and information professionals of the intersection between key patient safety philosophies and information, evidence and knowledge delivery mechanisms that support medical error reduction ; To raise awareness of the potential for systemic and individual information and knowledge sharing failures that are latent in the health care delivery process ; To explore the application of systemic improvement processes and tools to identify opportunities to reduce risk and potential for failure ; To provide evidence-based recommendations for health care information professionals and, with the knowledge they need to position themselves as partners with healthcare providers and leadership ; To illustrate how expertise from information and knowledge professionals folds into elements and language of the safety sciences ; To submit innovative activities and measures that illustrate a tangible contribution to patient safety from the knowledge transfer field.'--Publisher description.
Part 1. Context for innovation and improvement -- Patient safety: a brief but spirited history / Robert L. Wears, Kathleen M. Sutcliffe and Eric Van Rite -- Concepts, context, communication: who's on first? / Lorri Zipperer and Linda Williams -- Potential for harm due to failures in the EI&K process / Catherine K. Craven, Barbara Jones and Lorri Zipperer. -- Part 2. The role of evidence, information and knowledge -- Information and evidence failures in daily work: how they can affect the safety of care / Catherine K. Craven, Ross Koppel and Mark G. Weiner -- Leadership, EI&K and a culture of safety / Della Lin, Margo Farber and Judith Napier -- Weakness in the evidence base: latent problems to consider and solutions for improvement / Amanda Ross-White, Affaud Ana$1!XZ (BTanon and Sumant Ranji -- Part 3. Building blocks of safety that affect information, evidence and knowledge-sharing -- Systems thinking, complexity and EI&K for safe care / Howard Fuller -- Aviation contexts and EI&K innovation: reliability, teamwork and sensemaking / Jeff Brown, Sara Tompson and Lorri Zipperer -- Part 4. Practical applications to drive EI&K progress in the acute care environment -- EI&K sharing mechanisms in support of patient safety / Susan Carr, Barbara Olson and Lorri Zipperer -- Health information technology in hospitals: towards a culture of EI&K sharing / Prudence Dalrymple and Debora Simmons -- Critical intersections in patient safety: evidence and knowledge transfer at the sharp and blunt ends / Julia M. Esparza, Melissa Cole and Gunjan Kahlon -- Patient and families as vital EI&K conduits / Amy Donahue, Linda Kenney and Kathryn K. Leonhardt -- Humans and EI&K seeking: factors influencing reliability / Linda Williams and James P. Bagian -- Part 5. Future states -- Analyzing breakdowns in the EIK pathway / Barbara Jones, Mark Graber and Elaine Alligood -- A case to illustrate the opportunity for healthcare in EI&K enhancement / Grena Porto, Suzanne Graham and Lorri Zipperer.s
Includes bibliographical references (pages 275-325) and index.
Keywords: Patient Safety